Preparation method of functional fiber modifier, modifier and application of modifier in precast concrete

Through the preparation and application of functional fiber modifiers, the problems of insufficient early strength improvement of precast concrete and conventional early strength agents have been solved, and the early strength of precast concrete has been significantly improved, the later strength has been continuously increased, energy conservation and emission reduction and simplified process has been achieved. .

CN119461946APending Publication Date: 2025-02-18SHANDONG HUIDARUIHE BUILDING MATERIALS TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411599217.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, precast concrete has shortcomings in the early strength improvement, and there are problems such as poor workingability of concrete, insufficient development of later strength or even reverse shrinkage in the use of conventional early strength agents. At the same time, the steam maintenance process consumes a lot of energy and pollutes the environment, making it difficult to achieve. The concept of green, low-carbon and sustainable development.

Method used

Using the preparation method of functional fiber modifier, functional fibers are generated by reacting calcium and siliceous raw materials under specific conditions, and combined with special reinforcement agents to form functional fiber modifiers, which are applied in precast concrete to achieve steam-free cultivation. , rapid demolding and continuous growth in later strength.

Benefits of technology

The early strength of precast concrete has been significantly improved, the later strength has been continuously increased, energy conservation and emission reduction, and the process has been simplified, which has reduced energy consumption and improved the mechanical strength and temperature resistance of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461946A_ABST
    Figure CN119461946A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, and provides a preparation method of a functional fiber modifier, the modifier and application of the modifier in precast concrete.The method comprises the steps that S1, a calcium raw material is added into water to be stirred and mixed, sealed standing and aging are conducted for 20-48 h, a mixed solution is obtained, and the temperature of the water is controlled to range from 80 DEG C to 100 DEG C; s2, adding a siliceous raw material and a structure-directing agent into the mixed solution, uniformly mixing, and adding into a reaction kettle; s3, the temperature of the reaction kettle is controlled to rise, meanwhile, the stirring rotating speed is controlled to be 200-400 rpm, when the temperature rises to 180-220 DEG C, the stirring rotating speed is controlled to be 50-70 rpm, and heat preservation is conducted for a reaction; s4, after the reaction is finished, cooling, taking out slurry, filtering and drying to obtain functional fibers; and S5, dispersing the reinforcing agent in water, adding the functional fibers, and stirring for reaction to obtain the functional fiber modifier. According to the technical scheme of the invention, the functional fiber modifier has obvious rapid hardening and early strength effects, has no adverse effect on concrete performance, and can realize energy saving and steam curing-free and rapid demolding to improve the template turnover rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a method for preparing a functional fiber modifier, the modifier and application of the modifier in precast concrete. Background Art

[0002] In the related art, in the factory production of precast concrete components, in order to shorten the curing time, speed up the mold turnover, and improve production efficiency, the steam curing process is generally used to quickly improve the early strength of concrete to meet the strength requirements for demolding and lifting of precast components, or conventional early strength agents are added to achieve steam curing-free. There are the following technical defects:

[0003] (1) The steam curing process consumes a lot of energy and pollutes the environment. On the other hand, it is easy to cause thermal damage to concrete, resulting in risks such as reduced durability of concrete, which is not in line with the concept of green, low-carbon and sustainable development of concrete.

[0004] (2) Conventional early strength agents are not sufficient to improve the early strength of concrete to meet the requirements of prefabricated components, and there are problems such as poor concrete workability, insufficient late strength development, and even shrinkage during use. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art or related art.

[0006] To this end, the purpose of the present invention is to provide a preparation method of a functional fiber modifier, a modifier and its application in precast concrete. The functional fiber modifier has significant fast hardening and early strength effects and has no adverse effects on concrete performance. It can achieve energy saving and no steaming, and can quickly demold and improve the template turnover rate.

[0007] In order to achieve the above object, the technical solution of the present invention provides a method for preparing a functional fiber modifier, comprising the following steps:

[0008] S1, adding calcium raw materials into water, stirring and mixing, sealing and standing for aging for 20-48 hours to obtain a mixed solution, wherein the temperature of the water is controlled at 80-100°C;

[0009] S2, adding a siliceous raw material and a structure directing agent to the mixed solution, mixing them evenly and then adding them to a reaction kettle, wherein the mass ratio of the calcium raw material, water, the siliceous raw material and the structure directing agent is (3-10): (200-400): (2-8): (0.5-3), and the structure directing agent is at least one of hexadecyltrimethylammonium bromide (CTAB), ZrOCl2·8H2O, zircon (ZrSiO4), zirconium dioxide (ZrO2), V2O5, KOH or CaCl2, Sr(NO3)2, a polyether surfactant (F127), and sodium dodecyl sulfonate (SDS);

[0010] S3, controlling the reactor to heat up at a rate of 2-5°C / min, and controlling the stirring speed to 200-400rpm. When the temperature rises to 180-220°C, controlling the stirring speed to 50-70rpm, and keeping the temperature for 5-50h to react;

[0011] S4, after the reaction is completed, the temperature is cooled to 30-50°C, the slurry is taken out, filtered, and dried to obtain functional fibers, wherein the drying temperature is controlled at 50-70°C;

[0012] S5, dispersing the reinforcing agent in water, adding functional fiber, stirring and reacting at 25-45°C for 10-12 hours to obtain a functional fiber modifier, wherein the mass ratio of the reinforcing agent, water and functional fiber is (3-9): (50-70): (8-15).

[0013] Preferably, the enhancer used in step S5 is prepared by the following method:

[0014] S51, adding functional monomers and polyols to an organic solvent, adding alkaline materials, stirring at room temperature for 15-30 hours, cooling to 0°C, slowly dripping saturated salt solution into the reaction solution for extraction, concentrating the extract by evaporation, and separating by chromatography to obtain a reaction product A, wherein the mass ratio of functional monomers, polyols, organic solvents, and alkaline compounds is (80-120): (100-150): (9000-10000): (0.5-2.5);

[0015] S52, mixing the reaction product A, deionized water, and the alkaline compound at 60-150° C. for reaction, slowly adding the epoxy compound, and controlling the pressure in the reactor to be 0.2-0.8 MPa for hydrothermal reaction, cooling to room temperature after the reaction, and centrifugation drying to obtain a reaction product B, wherein the mass ratio of the reaction product A, deionized water, the alkaline compound, and the epoxy compound is: (100-120): (50-200): (0.3-0.8): (80-150);

[0016] S53, adding a functional modifier into deionized water, adding 0.05-0.2 mol / L of a buffer reagent to adjust the pH of the solution to 7-10, adjusting the reaction temperature of the solution to 40-60°C, adding the reaction product B into the mixed solution for reaction for 0.5-1.5h, then heating to 90-120°C for reaction for 2-8h, cooling to room temperature after the reaction is completed, adding ethanol for precipitation and centrifuging to obtain a sulfonic acid group-modified functional monomer, wherein the mass ratio of the functional modifier, deionized water, and the reaction product B is: (10-30): (20-80): (5-40);

[0017] S54, after mixing the sulfonic acid group modified functional monomer, polymer polysaccharide, unsaturated acid anhydride / ester and cross-linking agent, cross-linking reaction is carried out at 20-60°C for 10-16 hours to obtain an enhancer, wherein the mass ratio of the sulfonic acid group modified functional monomer, polymer polysaccharide, unsaturated acid anhydride / ester and cross-linking agent is: (5-30): (5-10): (15-60): (0.05-1).

[0018] Preferably, in step S51, the functional monomer is one or more of 4-hydroxybutyl vinyl ether, ethylene glycol monovinyl ether, 2-chloroethyl vinyl ether, and isopentyl glycol ether;

[0019] The polyol is one or more of propylene glycol, ethylene glycol, propylene glycol, glycerol, mannitol, xylitol, sorbitol, polyether diol, 1,2,4-butanetriol, and trihydroxymethylpropane; the organic solvent is any one of dimethyl sulfoxide, N-methylpyrrolidone, butanone, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, ethyl acetate, N,N-dimethylformamide, and acetone;

[0020] The alkaline material is one or more of lithium diisopropylamide, sodium hydride, sodium methoxide, potassium methoxide, sodium ethoxide, lithium diisopropylamide, butyl lithium, potassium ethoxide, sodium tert-butoxide, and sodium cyanide;

[0021] The saturated salt solution is any one of saturated solutions of sodium chloride, potassium bromide, ammonium sulfate, strontium nitrate, lithium chloride, magnesium chloride, barium chloride, magnesium nitrate and potassium chloride.

[0022] Preferably, in step S52, the alkaline compound is one or more of N-methyldiethanolamine, diglycolamine, dimethylethanolamine, and triethanolamine;

[0023] The epoxy compound is one or more of propylene oxide, butylene oxide, ethylene oxide, epichlorohydrin, propyl ethylene oxide, and methyl propylene oxide.

[0024] Preferably, in step S53, the functional modifier is one or more of methanedisulfonic acid disodium salt, sodium styrene sulfonate, sodium alkyl sulfonate, sodium alkylbenzene sulfonate, sodium vinyl sulfonate, sodium propylene sulfonate, sodium methyl propylene sulfonate, sodium styrene sulfonate, 2-acrylamide-2-methylpropane sulfonic acid, sodium alkyl sulfate, sodium alkyl naphthalene sulfonate, sodium alkyl succinate sulfonate, and sodium aminosulfonate;

[0025] The buffer reagent is at least one of hydroxymethylaminomethane-hydrochloric acid buffer, potassium dihydrogen phosphate-disodium hydrogen phosphate, boric acid-borax, N-2-hydroxyethylpiperazineethanesulfonic acid buffer, glycine-sodium hydroxide, trishydroxymethylaminomethane hydrochloride, acetic acid-sodium acetate, 2-(N-morpholino)ethanesulfonic acid, disodium hydrogen phosphate-citric acid, and phosphate buffer solution.

[0026] Preferably, in step S54, the polymer polysaccharide is one or more of sodium alginate, dextran sulfate, sodium carboxymethyl cellulose, sodium cellulose sulfate, sodium cellulose carboxylate, carboxycellulose, carboxymethyl chitosan, potassium carboxymethyl cellulose, guar gum, xanthan gum, carrageenan, carboxymethyl cellulose, and methyl cellulose, wherein the carboxymethyl chitosan is selected from O-carboxymethyl chitosan or N,O-carboxymethyl chitosan;

[0027] The unsaturated acid anhydride / ester is one or more of acrylic anhydride, 1,3-butanediol dimethacrylate, 1,3-butanediol diacrylate, methacrylic anhydride, ethylene glycol dimethacrylate, methyl methacrylate, ethyl methacrylate, 1,4-butanediol dimethacrylate, 1,4-butanediol diacrylate, ethylene glycol diacrylate, 1,3-propylene glycol dimethacrylate, and 1,3-propylene glycol diacrylate;

[0028] The cross-linking agent is one of persulfate, water-soluble azo compound and peroxide, wherein the persulfate is one or more of sodium peroxydisulfate, benzoyl peroxide, potassium peroxydisulfate, ammonium persulfate, sodium persulfate, sodium permonosulfate and potassium permonosulfate; the water-soluble azo compound is one or more of azobisisobutylamidine hydrochloride or 2,2'-azo[2-(2-imidazoline-2-yl)propane] dihydrochloride, azobisisobutyric acid and azobisisobutylamidine; the peroxide is one or more of hydrogen peroxide, peroxycarboxylic acid and perborate.

[0029] Preferably, the calcium raw material is one or more of quicklime, calcium carbonate, calcium nitrate, calcium formate, calcium acetate, calcium chloride, calcium gluconate, calcium hydrogen phosphate, calcium lactate, and calcium chloride;

[0030] The siliceous raw material is one or more of silica gel, silicon oxide, powdered quartz, silica fume, tetraethoxysilane (TEOS), silicon micropowder, analytically pure SiO2, sodium silicate, sodium metasilicate pentahydrate, potassium silicate, sodium metasilicate nonahydrate, and lithium silicate.

[0031] The technical solution of the present invention further provides a functional fiber modifier, which is obtained by using any of the functional fiber modifier preparation methods in the above technical solutions.

[0032] The technical solution of the present invention also provides an application of a functional fiber modifier in steam-free precast concrete, comprising the following steps:

[0033] Weigh component materials according to the raw material formula and set aside, wherein the raw material formula includes the following component materials in parts by weight: 220-350 parts of cementitious material, 700-1050 parts of coarse aggregate, 500-850 parts of fine aggregate, 40-100 parts of admixture, 40-70 parts of functional fiber modifier and 50-70 parts of water, wherein the cementitious material includes organic cementitious material and inorganic cementitious material, wherein the mass ratio of inorganic cementitious material to organic cementitious material is 3:1;

[0034] Firstly, coarse aggregate, fine aggregate and admixture are added into a forced mixer, and then inorganic gelling material is added and stirred to obtain a mixture;

[0035] The functional fiber modifier is added into the mixture, and the mixture is stirred while being injected. Then, water and organic cementitious materials are added and the mixture is stirred continuously to obtain the steam-free precast concrete.

[0036] Preferably, the inorganic cementitious material is one or more of silicate cement, aluminate cement, sulphoaluminate cement, lime or gypsum;

[0037] The organic gelling material is one or more of polyacrylate emulsion, water-based acrylic resin, polyvinyl alcohol, water-based polyurethane resin, styrene-butadiene emulsion, vinyl laurate copolymer redispersible latex powder, water-based epoxy resin, guar gum, acrylic acid or acrylate homopolymer or copolymer redispersible latex powder, water-based alkyd resin, silicone-acrylic redispersible latex powder, ethylene-vinyl acetate copolymer emulsion, water-based fluorocarbon resin, and EVA dispersible rubber powder, wherein the EVA dispersible rubber powder is ethylene-vinyl acetate copolymer or homopolymer, and the ethylene content is higher than the vinyl acetate content; the polyvinyl alcohol is PVA1788, and its particle size is greater than 100 mesh;

[0038] The admixture is one or more of fly ash, mineral powder, volcanic ash, silica powder or limestone powder.

[0039] The present invention provides a method for preparing a functional fiber modifier, a modifier and application in precast concrete, which have the following beneficial technical effects:

[0040] (1) The preparation method of a functional fiber modifier proposed by the present invention is simple and reliable. The functional fiber is dispersed in an aqueous solution of a special reinforcing agent, and the two are compounded. The obtained functional fiber modifier can achieve steam-free curing, rapid demoulding, and continuous increase in late strength of precast concrete.

[0041] (2) The functional fiber modifier proposed in the present invention is a crystalline fiber material with calcium silicate as the main component. When mixed into a precast concrete matrix, it can improve the mechanical strength and temperature resistance of the material while maintaining a low thermal conductivity and improving thermal insulation performance.

[0042] (3) When the functional fiber modifier proposed in the present invention is used in precast concrete, the introduction of micro-nanoscale calcium silicate crystal fibers can effectively shorten the setting time of cement paste and significantly improve its strength properties. In the cement paste system, calcium ions and silicate ions, through the electrostatic interaction mechanism, induce and generate the initial CSH gel phase on the surface of specific nucleation sites. This process significantly reduces the energy barrier for CSH gel nucleation and accelerates its formation rate. At the same time, the lower concentration of H2SiO4 in the paste 2- Anions can be adsorbed onto the surface of the crystal nucleus, thereby catalyzing and promoting the growth and deposition of CSH gel. This effect further promotes the dissolution of the silicate phase and the formation of hydration products, which is beneficial to the rapid construction of the early microstructure of the cement paste and the continuous development of its strength properties.

[0043] (4) The functional fiber modifier proposed in the present invention uses a special reinforcing agent to disperse the functional fiber. The sulfonic acid group-modified functional monomer of the special reinforcing agent adopts a sulfonic acid group-terminated alkenyl polyether monomer containing a multi-branched structure, which increases the content of branched groups. The increased content of sulfonic acid groups further improves the dispersibility and retention capacity of the reinforcing agent for cement in concrete.

[0044] (5) The functional fiber modifier proposed in the present invention uses a special reinforcing agent to disperse the functional fiber. The special reinforcing agent induces hydration products through the network structure effect formed by the polysaccharide molecular chain segments and its functional functional groups such as carboxyl, amino, and sulfonic acid groups, constructs local hardening areas, and significantly improves and accelerates the hydration process. At the same time, the carboxyl, amino, and sulfonic acid groups on the main chain and grafted chain of its molecular structure form multiple adsorption sites, which fully exert the water-reducing and dispersing effects.

[0045] (6) The functional fiber modifier proposed in the present invention is applied to precast concrete, which does not require steam curing process, simplifies the precast concrete process, reduces energy consumption, and can significantly improve the internal density of precast concrete components, optimize their surface flatness, and effectively inhibit the generation of cracks. At the same time, it ensures that the raw materials of precast concrete components maintain stable strength characteristics in the later stage, thereby comprehensively enhancing their overall structural strength.

[0046] (7) The functional fiber in the functional fiber modifier proposed in the present invention is calcium sulfonate fibrous whiskers, which can promote the formation of the early microstructure of cement paste, accelerate the hydration reaction, and shorten the setting time. The special reinforcing agent has a sulfonic acid functional group. When added to the cement system, it can form hydrogen bonds with water molecules in the liquid phase, play a role in strengthening spatial steric hindrance, and can promote the hydration of C3S and the formation of calcium sulfonate crystals. At the same time, the sulfonic acid group plays a role in accelerating coagulation. The introduction of the reinforcing agent with a sulfonic acid group can improve the early hydration process of cement and further shorten the setting time of cement paste.

[0047] Additional aspects and advantages of the present invention will be given in part in the following description and, in part, will be obvious from the following description or learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0049] Figure 1 XRD patterns of functional fibers according to embodiments of the present invention are shown, wherein (a) Embodiment 1, (b) Embodiment 2, and (c) Embodiment 3;

[0050] Figure 2 SEM images of functional fibers according to embodiments of the present invention are shown, wherein (a) Embodiment 1, (b) Embodiment 2, and (c) Embodiment 3;

[0051] Figure 3 The EDS spectrum of the functional fiber according to Example 1 of the present invention is shown;

[0052] Figure 4 A comparison diagram of cement paste setting time according to an embodiment of the present invention and a comparative example is shown;

[0053] Figure 5 SEM images of precast concrete components according to Example 1 and Comparative Example 1 of the present invention are shown;

[0054] Figure 6 A comparison diagram of the splitting tensile strength of precast concrete components according to an embodiment of the present invention and a comparative example is shown. DETAILED DESCRIPTION

[0055] The present invention discloses a method for preparing a functional fiber modifier, a modifier and its application in precast concrete. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve the desired effect. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in the present invention. The method and application of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the method and application described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0056] The present invention will be further described below in conjunction with embodiments:

[0057] Example 1

[0058] A method for preparing a functional fiber modifier comprises the following steps:

[0059] S102, Preparation of enhancer

[0060] S1021, adding 80 parts of ethylene glycol monovinyl ether and 100 parts of propylene glycol to 9000 parts of N-methylpyrrolidone, adding 1 part of sodium methoxide, stirring at room temperature for 15 hours, lowering the temperature of the reactant to 0°C, slowly dropping a saturated potassium chloride salt solution into the reaction solution for extraction, concentrating the extract by evaporation, and separating by chromatography to obtain a reaction product A;

[0061] S1022, 100 parts of the reaction product A are mixed with 80 parts of deionized water and 0.3 parts of diglycolamine at 60° C., 80 parts of propyl ethylene oxide are slowly added for hydrothermal reaction, the pressure in the reactor is controlled to be 0.4 MPa, the reaction is completed, the reaction is cooled to room temperature, and the reaction product B is obtained by centrifugal drying;

[0062] S1023, adding 10 parts of sodium propylene sulfonate to 20 parts of deionized water, adding 0.05 mol / L potassium dihydrogen phosphate-disodium hydrogen phosphate buffer reagent to adjust the solution pH to 7.5, adjusting the solution reaction temperature to 40° C., adding 10 parts of reaction product B to the mixed solution to react for 0.5 h, then heating to 90° C. to react for 3 h, cooling to room temperature after the reaction is completed, adding ethanol to precipitate, and centrifuging to obtain a sulfonic acid group-modified functional monomer;

[0063] S1024, 10 parts of sulfonic acid group-modified functional monomer, 5 parts of dextran sulfate, 15 parts of 1,3-butanediol diacrylate, and 0.05 parts of sodium persulfate are mixed and cross-linked at 30° C. for 10 hours to obtain a reinforcing agent.

[0064] S104, Preparation of functional fiber modifier

[0065] S1041, adding 3 parts of calcium nitrate raw material to 200 parts of warm water at 80°C for stirring and digestion, and sealing and placing the mixture for aging for 22 hours;

[0066] S1042, add 3 parts of silica gel raw material to the reaction solution, add 0.5 parts of polyether surfactant (F127), mix well and add to the autoclave;

[0067] S1043, raising the temperature of the autoclave at a rate of 2°C / min, setting the stirring speed to 200 rpm, raising the temperature to 180°C, reducing the stirring speed to 50 rpm, and maintaining the temperature for 20 hours to keep the reaction under high temperature and high pressure. After the reaction is completed, cooling to 30°C, taking out the slurry, filtering it, and drying it in a vacuum drying oven at 50°C to obtain functional fibers;

[0068] S1044, disperse 3 parts of reinforcing agent in 50 parts of water, add 10 parts of functional fiber, stir and react at 25°C for 10 hours to obtain a functional fiber modifier.

[0069] S106, Preparation of precast concrete without steam curing

[0070] S1061, weigh 180 parts of Portland cement, 60 parts of waterborne polyurethane resin, 700 parts of coarse aggregate, 500 parts of fine aggregate, 60 parts of fly ash, 40 parts of functional fiber modifier and 60 parts of water, and set aside;

[0071] S1062, using a forced mixer, dry mixing first and then wet mixing, first adding coarse aggregate, fine aggregate and fly ash, adding the formulated amount of silicate cement, stirring and mixing to obtain a mixture;

[0072] S1063, adding the functional fiber modifier as mixing water into the mixture, stirring while injecting, adding water and waterborne polyurethane resin and continuing to stir, to obtain steam-free precast concrete.

[0073] Example 2

[0074] A method for preparing a functional fiber modifier comprises the following steps:

[0075] S202, Preparation of Enhancer

[0076] S2021, adding 100 parts of 4-hydroxybutyl vinyl ether and 120 parts of mannitol to 9100 parts of N-methyl-2-pyrrolidone, adding 1.5 parts of lithium diisopropylamide, stirring at room temperature for 20 hours, lowering the temperature of the reactant to 0°C, slowly adding a saturated ammonium sulfate solution dropwise to the reaction solution for extraction, concentrating the extract by evaporation, and separating by chromatography to obtain a reaction product A;

[0077] S2022, 110 parts of the reaction product A are mixed with 150 parts of deionized water and 0.5 parts of dimethylethanolamine at 80° C., 100 parts of methyl propylene oxide are slowly added for hydrothermal reaction, the pressure in the reactor is controlled to be 0.6 MPa, the reaction is completed, the reaction is cooled to room temperature, and the reaction product B is obtained by centrifugal drying;

[0078] S2023, adding 15 parts of sodium styrene sulfonate to 40 parts of deionized water, adding 0.1 mol / L tris(hydroxymethyl)aminomethane hydrochloride to adjust the solution pH to 8, adjusting the solution reaction temperature to 50°C, adding 10 parts of reaction product B to the mixed solution to react for 1 hour, then heating to 100°C to react for 4 hours, cooling to room temperature after the reaction is completed, adding ethanol to precipitate and centrifuging to obtain a sulfonic acid group-modified functional monomer;

[0079] S2024, 15 parts of sulfonic acid group-modified functional monomer, 8 parts of carboxymethyl cellulose, 55 parts of methyl methacrylate, and 0.1 parts of benzoyl peroxide were mixed and cross-linked at 40° C. for 12 hours to obtain a reinforcing agent.

[0080] S204, Preparation of functional fiber modifier

[0081] S2041, adding 5 parts of calcium gluconate raw material to 250 parts of warm water at 90° C. for stirring and digestion, and sealing and placing it for aging for 30 hours;

[0082] S2042, add 5 parts of powdered quartz to the reaction solution, add 1 part of sodium dodecyl sulfate (SDS), mix well and add to the autoclave;

[0083] S2043, raising the temperature of the autoclave at a rate of 3°C / min, setting the stirring speed to 300 rpm, raising the temperature to 200°C, reducing the stirring speed to 60 rpm, and maintaining the temperature for 30 hours to keep the reaction under high temperature and high pressure. After the reaction is completed, cooling to 40°C, taking out the slurry, filtering it, and drying it in a vacuum drying oven at 60°C to obtain functional fibers;

[0084] S2044, disperse 5 parts of the reinforcing agent in 60 parts of water, add 12 parts of the functional fiber, stir and react at 30°C for 11 hours to obtain a functional fiber modifier.

[0085] S206, Preparation of precast concrete without steam curing

[0086] S2061, weigh 195 parts of sulphoaluminate cement, 65 parts of guar gum, 800 parts of coarse aggregate, 650 parts of fine aggregate, 70 parts of volcanic ash, 60 parts of functional fiber modifier and 65 parts of water, and set aside;

[0087] S2062, using a forced mixer, dry mixing first and then wet mixing, first adding coarse aggregate, fine aggregate and volcanic ash, adding the formula amount of sulphoaluminate cement, stirring and mixing to obtain a mixture;

[0088] S2063, add the functional fiber modifier as mixing water into the mixture, stir while injecting, add water and guar gum and continue stirring to obtain steam-free precast concrete.

[0089] Example 3

[0090] A method for preparing a functional fiber modifier comprises the following steps:

[0091] S302, Preparation of enhancer

[0092] S3021, adding 120 parts of isopentyl glycol ether and 150 parts of 1,2,4-butanetriol to 9600 parts of butanone, adding 2 parts of potassium ethoxide, stirring at room temperature for 25 hours, lowering the temperature of the reactant to 0°C, slowly dripping a saturated lithium chloride salt solution into the reaction solution for extraction, concentrating the extract by evaporation, and separating by chromatography to obtain a reaction product A;

[0093] S3022, 120 parts of the reaction product A are mixed with 180 parts of deionized water and 0.8 parts of N-methyldiethanolamine at 120° C., 150 parts of butylene oxide are slowly added for hydrothermal reaction, the pressure in the reactor is controlled to be 0.8 MPa, the reaction is completed, the reaction is cooled to room temperature, and centrifugation is performed to obtain a reaction product B;

[0094] S3023, adding 30 parts of sodium alkyl succinate sulfonate to 80 parts of deionized water, adding 0.2 mol / L acetic acid-sodium acetate to adjust the pH of the solution to 9, adjusting the reaction temperature of the solution to 60°C, adding 10 parts of the reaction product B to the mixed solution to react for 1.5 hours, then heating to 120°C to react for 8 hours, cooling to room temperature after the reaction is completed, adding ethanol to precipitate and centrifuging to obtain a sulfonic acid group-modified functional monomer;

[0095] S3024, 30 parts of sulfonic acid group modified functional monomer, 10 parts of sodium cellulose carboxylate, 60 parts of 1,3-propylene glycol dimethacrylate, and 0.5 parts of perborate were mixed and cross-linked at 60° C. for 16 hours to obtain a reinforcing agent.

[0096] S304, Preparation of functional fiber modifier

[0097] S3041, adding 10 parts of calcium acetate raw material into 400 parts of warm water at 100° C. for stirring and digestion, and sealing and placing the mixture for aging for 48 hours;

[0098] S3042, add 8 parts of lithium silicate to the reaction solution, add 2 parts of zirconium dioxide (ZrO2), mix well and add to the autoclave;

[0099] S3043, raising the temperature of the autoclave at a rate of 5°C / min, setting the stirring speed to 400 rpm, raising the temperature to 220°C, reducing the stirring speed to 70 rpm, and maintaining the temperature for 50 hours to keep the reaction under high temperature and high pressure. After the reaction is completed, cooling to 50°C, taking out the slurry, filtering it, and drying it in a vacuum drying oven at 70°C to obtain functional fibers;

[0100] S3044, 9 parts of the reinforcing agent are dispersed in 70 parts of water as a dispersant, 15 parts of the functional fiber are added, and the mixture is stirred and reacted at 45° C. for 12 hours to obtain a functional fiber modifier.

[0101] S306, Preparation of precast concrete without steam curing

[0102] S3061, weigh 210 parts of aluminate cement, 70 parts of vinyl laurate copolymer redispersible latex powder, 1000 parts of coarse aggregate, 800 parts of fine aggregate, 100 parts of silica fume, 70 parts of functional fiber modifier and 70 parts of water, and set aside;

[0103] S3062, using a forced mixer, dry mix first and then wet mix, first add coarse aggregate, fine aggregate and volcanic ash, add the formulated amount of aluminate cement, stir and mix well to obtain a mixture;

[0104] S3063, adding the functional fiber modifier as mixing water into the mixture, stirring while injecting, adding water and vinyl laurate copolymer redispersible latex powder and continuing to stir, to obtain steam-free precast concrete.

[0105] Example 4

[0106] The difference from Example 1 is that the preparation of the steam-free precast concrete is specifically as follows:

[0107] S4061, weigh 240 parts of aluminate cement, 80 parts of vinyl laurate copolymer redispersible latex powder, 1000 parts of coarse aggregate, 800 parts of fine aggregate, 100 parts of silica fume, 60 parts of functional fiber modifier and 70 parts of water for later use;

[0108] S4062, using a forced mixer, dry mix first and then wet mix, first add coarse aggregate, fine aggregate and volcanic ash, add the formulated amount of aluminate cement, stir and mix well to obtain a mixture;

[0109] S4063, adding the functional fiber modifier as mixing water into the mixture, stirring while injecting, adding water and vinyl laurate copolymer redispersible latex powder and continuing to stir, to obtain steam-free precast concrete.

[0110] Example 5

[0111] The difference from Example 1 is that the preparation of the steam-free precast concrete is specifically as follows:

[0112] S5061, weigh 240 parts of aluminate cement, 80 parts of vinyl laurate copolymer redispersible latex powder, 1000 parts of coarse aggregate, 800 parts of fine aggregate, 100 parts of silica fume, 50 parts of functional fiber modifier and 70 parts of water, and set aside;

[0113] S5062, using a forced mixer, dry mix first and then wet mix, first add coarse aggregate, fine aggregate and volcanic ash, add the formulated amount of aluminate cement, stir and mix well to obtain a mixture;

[0114] S5063, adding the functional fiber modifier as mixing water into the mixture, stirring while injecting, adding water and vinyl laurate copolymer redispersible latex powder and continuing to stir, to obtain steam-free precast concrete.

[0115] Comparative Example 1

[0116] The difference from Example 1 is that in the preparation of the steam-free precast concrete, an equal amount of water is used to replace the functional fiber modifier. Specifically,

[0117] 1) Weigh 180 parts of Portland cement, 60 parts of waterborne polyurethane resin, 700 parts of coarse aggregate, 500 parts of fine aggregate, 60 parts of fly ash, and 110 parts of water for later use;

[0118] 2) using a forced mixer, first dry mixing and then wet mixing, first adding coarse aggregate, fine aggregate and fly ash, then adding the formulated amount of silicate cement, stirring and mixing to obtain a mixture;

[0119] 3) adding water and waterborne polyurethane resin into the mixture prepared in step 2), stirring while injecting, and obtaining steam-free precast concrete.

[0120] Comparative Example 2

[0121] The difference from Example 1 is that there is no reinforcing agent in the preparation process, and the reinforcing agent is not added in the preparation process of the functional fiber modifier. Specifically,

[0122] (1) Add 3 parts of calcium nitrate raw material to 200 parts of warm water at 80° C., stir and digest, and seal and place to age for 22 hours;

[0123] (2) Add 3 parts of silica gel raw material to the reaction solution, add 0.5 parts of polyether surfactant (F127), mix well and add to the autoclave;

[0124] (3) The high-pressure reactor was heated at a rate of 2°C / min, the stirring speed was set to 200 rpm, the temperature was raised to 180°C, the stirring speed was reduced to 50 rpm, and the temperature was kept for 20 h to keep the reaction under high temperature and high pressure. After the reaction was completed, the temperature was lowered to 30°C, the slurry was taken out, filtered, and dried in a vacuum drying oven at 50°C to obtain functional fibers;

[0125] (4) 10 parts of functional fiber were added to 50 parts of water as a dispersant, and the mixture was stirred at 25°C for 10 hours to obtain a functional fiber modifier.

[0126] Comparative Example 3

[0127] The difference from Example 1 is that the precast concrete is prepared without steam curing, and the cementitious materials are all inorganic cementitious materials. Specifically,

[0128] 1) Weigh 240 parts of Portland cement, 700 parts of coarse aggregate, 500 parts of fine aggregate, 60 parts of fly ash, 50 parts of functional fiber modifier and 60 parts of water for later use;

[0129] 2) Using a forced mixer, dry mix first and then wet mix, first add coarse aggregate, fine aggregate and fly ash, add silicate cement and stir to obtain a mixture;

[0130] 3) The functional fiber modifier is used as mixing water and added into the mixture, and the mixture is stirred while being injected. After the water is added, the stirring is continued to obtain the steam-free precast concrete.

[0131] Results Analysis

[0132] X-ray diffraction and electron microscope scanning were performed on the functional fibers synthesized using three different calcium sources and silicon sources in Examples 1 to 3. The results are as follows: Figure 1 and Figure 2 shown.

[0133] like Figure 1 As shown in Figure 2, according to the XRD analysis results of the product mineral composition, it can be confirmed that under the hydrothermal synthesis conditions, the products synthesized using three different calcium sources and silicon sources have the main crystal phase of calcite (Ca6Si6O 17 (OH)2), which is consistent with the JCPDS standard card number 23-0125. By comparing and analyzing the XRD patterns of these three examples, it can be observed that all products prepared by the hydrothermal synthesis method show strong diffraction peaks and fewer impurity peaks, which indicates that the crystallinity of the calcite crystal is high and has good crystallization properties.

[0134] like Figure 2 As shown, different types of calcium sources have a significant effect on the microstructure of the hydrothermal synthesis product. Specifically, Example 1 synthesized fibrous whiskers of calcite with a high aspect ratio (50-100). In contrast, the calcium sources used in Examples 2 and 3 resulted in a decrease in the aspect ratio of the obtained fibrous hydrothermal synthesis product. In the CaO-SiO2-H2O system, calcite crystals are directly transformed and formed via CSH (calcium-silicon ratio calcium silicate hydrate). Different types of calcium sources and silicon sources introduce different ions into the CaO-SiO2-H2O system. These ions play different roles in the formation and structural regulation of CSH. Some ions promote the crystallization process of CSH, some ions can be integrated into the structural framework of CSH, and other ions contribute to the stability of the CSH structure. Examples 1, 2, and 3 introduced calcium nitrate, calcium gluconate, and calcium acetate into the CaO-SiO2-H2O system, respectively.

[0135] Based on the above X-ray diffraction (XRD) and SEM analysis results, it can be inferred that under hydrothermal conditions, the introduction of NO3-, gluconate ions and acetate ions into the CaO-SiO2-H2O system did not change the crystal phase structure of the hydrothermal synthesis products, and the products were all fibrous.

[0136] Energy dispersive spectroscopy (EDS) analysis was performed on the functional fiber synthesized in Example 1. The results are as follows: Figure 3As shown, no other elements were detected in the synthesized product except Ca, Si, and O. Therefore, the SEM and EDS analysis results are consistent with the XRD analysis results, indicating that the three examples have successfully synthesized fibrous wollastonite crystals.

[0137] The setting time of cement paste was tested for Examples 1 to 5 and Comparative Examples 1 and 2. The testing process was carried out with reference to the setting time of cement paste in GB / T 1346-2011. The test results are as follows: Figure 4 shown.

[0138] like Figure 4 As shown, compared with comparative example 1, the initial setting and final setting times of comparative example 2 are shortened, the initial setting time is reduced from 340min to 300min, and the final setting time is reduced from 340min to 300min. This is because the addition of fibrous calcium silicate-type functional fibers promotes the formation of early microstructures, accelerates the hydration reaction, and shortens the setting time. Compared with comparative example 2, the initial setting time of Examples 1 to 5 of the present invention is significantly shortened. This is because the reinforcing agent has a sulfonic acid functional group, which can be added to the cement system to form hydrogen bonds with water molecules in the liquid phase, play a role in strengthening steric hindrance, and can promote the hydration of C3S and the formation of calcium sulfate crystals; at the same time, the sulfonic acid group plays a role in accelerating coagulation. The reinforcing agent introduced with the sulfonic acid group can improve the early hydration process of cement and further shorten the setting time of cement paste. In Example 5, Example 1 is compared with Example 4. The amount of functional fiber modifier added increases, and its initial setting and final setting times are significantly shortened. The reason is that the more functional fiber modifier is added, the easier it is to accelerate the generation of hydration products, and the cement paste can form a stable structure earlier. The continuous generation of hydration products promotes the continuous compactness of the internal structure, the rapid reduction of the setting time, and the continuous increase of strength. Therefore, the functional fiber modifier can promote the hydration reaction of early cement and generate hydration products earlier. Therefore, the time for the slurry to lose plasticity becomes shorter. However, the amount of functional fiber modifier added cannot be too much, and too much can easily lead to early cracking of concrete.

[0139] The compressive strength test was performed on the steam-curing-free precast concrete of Examples 1 to 5 and Comparative Examples 1 to 3. The test results are shown in Table 1 below.

[0140] Table 1 Compressive strength test results of precast concrete components without steam curing

[0141] serial number 1d(MPa) 3d(MPa) 28d(MPa) Comparative Example 1 6.3 16.3 25.3 Comparative Example 2 9.5 21.5 28.9 Comparative Example 3 10.3 18.5 28.2 Example 1 15.6 35.3 46.9 Example 2 16.2 36.2 47.2 Example 3 16.5 37.3 47.8 Example 4 18.9 40.5 52.3 Example 5 13.5 28.2 37.5

[0142] As can be seen from Table 1, the embodiments of the present invention have higher early strength characteristics. This strengthening effect is mainly attributed to the following three factors: first, the early strength effect of the functional fiber, and second, the accelerating effect of the reinforcing agent containing the sulfonic acid group. The introduction of the sulfonic acid reinforcing agent accelerates the hydration process of cement, and works together with the functional fiber to significantly improve the early strength of concrete. Third, the organic-inorganic composite cementitious material used in the present invention achieves tight chemical consolidation of coarse and fine aggregates by making full use of the hydration reaction of the inorganic cementitious material and the physicochemical reaction of the organic cementitious material. This process not only increases the generation of hydration products such as CSH (calcium silicate hydrate) and CAH (calcium aluminate hydrate), but also enhances the interfacial bonding force between different aggregates, improves the compactness of the microstructure, and thus achieves a significant improvement in mechanical strength.

[0143] In addition, compared with the control example, regardless of the content of the functional fiber modifier in the embodiment of the present invention, the early strength of the concrete at 1 day and 3 days and the late strength at 28 days are all higher than those in the control example. This is mainly attributed to the promoting effect of the calcium silicate fiber seeds contained in the functional fiber modifier on cement hydration, and the reinforcing agent has a sulfonic acid functional group, which can form hydrogen bonds with water molecules when added to the cement system, play a role in strengthening steric hindrance, and promote the hydration of C3S in cement and the formation of calcium aluminate crystals. These seeds promote the dissolution of cement mineral ions and accelerate the development of early microstructures, thereby improving the early performance of concrete. During the cement hydration process, chemical bonds such as O-Ca-O and O-Si-O are broken, releasing sulfate, calcium ions, hydroxide ions and H2SiO4 2- Among them, H2SiO4 dissolved from silicate phase 2- It is the key nucleation site for the formation of CSH gel. Calcium ions in cement paste are adsorbed to the surface of these nucleation sites through electrostatic action to form the initial CSH gel. The addition of functional fiber modifier is equivalent to providing a large number of nucleation sites, which form hydration products faster through ion adsorption, thereby reducing the nucleation barrier of CSH gel. The addition of functional fiber modifier allows the solution to begin nucleation on the surface of the crystal nucleus at a lower saturation concentration to form hydration products. The local generation of hydration products leads to a concentration difference inside the slurry, which further promotes the dissolution of ions and accelerates the formation process of CSH gel. In summary, functional fibers and reinforcing agents have significant synergistic effects, which are mainly reflected in that when added to the cement mixing system, the sulfonic acid hydrophilic groups of the reinforcing agent will react with the solvent water to form a hydration film, and some ions will form hydrogen bonds with water molecules to further enhance the hydrophilicity of the hydration film; functional fibers accelerate the destruction of the hydration film, while increasing the contact area between C2S and C3S and water, it will accelerate the formation of calcium ions, hydroxide ions and H2SiO4 2-At the same time, the functional fiber modifier acts as a nucleating agent to improve ion adsorption and promote the hydration reaction. The functional fiber and the reinforcing agent synergistically significantly improve the early hydration reaction process, thereby improving the early strength of precast concrete.

[0144] By comparing Example 5, Example 1 and Example 4, it can be found that the more the amount of functional fiber modifier added, the more the number of functional fiber seeds contained therein, which is more conducive to improving the early strength of concrete and the continuous development of late strength. The cement samples with a curing age of 24 hours in Comparative Example 1 and Example 1 were selected for microstructure analysis. The results are as follows: Figure 5 As shown, the microstructure of the hardened cement paste mixed with the functionalized fiber modifier is significantly different from that of the comparative example 1 without the functionalized fiber modifier. In comparative example 1, the observed hydration products are arranged in a disordered manner, accompanied by the generation of a large number of coarse long-flaked calcium sulfonate, and at the same time, the formed hydrated calcium silicate gel (CSH) is connected to each other to form a whole, but its morphological characteristics are not prominent. In contrast, in the cement sample mixed with the functionalized fiber modifier, only a small amount of long-flaked calcium sulfonate crystals are observed, and the hexagonal plate-like calcium hydroxide crystals are clearly visible, and the hydrated calcium silicate gel is distributed in the sample in a clustered form. The functionalized fiber modifier prepared by the present invention mainly comprises calcium silicate seeds, and such fibrous seeds show excellent induced nucleation effect. When these seeds are added to the cement paste, they can effectively reduce the nucleation energy barrier of cement hydration products, hydrated calcium silicate gel and calcium hydroxide. As the cement mineral dissolves and releases various types of reactive ions, the hydration products tend to grow on the surface of these seeds. Therefore, this may be the fundamental reason for the formation of a more uniform cluster distribution of calcium silicate hydrate gel in the hardened cement paste in the experimental group.

[0145] According to the test specification of "Standard for Mechanical Properties of Ordinary Concrete" (GB / T50081-2019), a standard cubic test block with a side length of 150mm was used. The test specimens used were cast in the same batch as the compressive strength test specimens and had the same curing conditions. The splitting tensile strength test used the same test equipment as the compressive strength test. The test results are as follows Figure 6 shown.

[0146] like Figure 6As shown, compared with comparative example 1, in the embodiment, as the amount of functional fiber modifier added increases, the splitting tensile strength of the sample is significantly enhanced. This is mainly because the chemical composition of the functional fiber modifier is similar to that of the concrete matrix, resulting in a chemical reaction between the fiber and the matrix. The calcium silicate fiber can inhibit the development of cracks at the microscopic level. At the same time, the fiber itself can be used as a nucleation site to promote cement hydration and gelation. The growth and consolidation of hydration products on the fiber surface strengthen the bonding ability between cement particles to a certain extent, and improve the chemical bonding strength between the two. At the same time, the calcium silicate fiber has the characteristics of low friction bonds and low slip hardening coefficient. The combined effect of these two aspects significantly improves the splitting tensile strength of the embodiment compared with the comparative example.

[0147] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a functional fiber modifier, characterized in that: The following steps are involved: S1, adding calcium raw materials into water, stirring and mixing, sealing and standing for aging for 20-48 hours to obtain a mixed solution, wherein the temperature of the water is controlled at 80-100°C; S2, adding a siliceous raw material and a structure directing agent to the mixed solution, mixing them evenly and then adding them to a reaction kettle, wherein the mass ratio of the calcium raw material, water, the siliceous raw material and the structure directing agent is (3-10): (200-400): (2-8): (0.5-3), and the structure directing agent is at least one of hexadecyltrimethylammonium bromide (CTAB), ZrOCl2·8H2O, zircon (ZrSiO4), zirconium dioxide (ZrO2), V2O5, KOH or CaCl2, Sr(NO3)2, a polyether surfactant (F127), and sodium dodecyl sulfonate (SDS); S3, controlling the reactor to heat up at a rate of 2-5°C / min, and controlling the stirring speed to 200-400rpm. When the temperature rises to 180-220°C, controlling the stirring speed to 50-70rpm, and keeping the temperature for 5-50h to react; S4, after the reaction is completed, the temperature is cooled to 30-50°C, the slurry is taken out, filtered, and dried to obtain functional fibers, wherein the drying temperature is controlled at 50-70°C; S5, dispersing the reinforcing agent in water, adding functional fiber, stirring and reacting at 25-45°C for 10-12 hours to obtain a functional fiber modifier, wherein the mass ratio of the reinforcing agent, water and functional fiber is (3-9): (50-70): (8-15).

2. The method for preparing a functional fiber modifier according to claim 1, characterized in that: The enhancer used in step S5 is prepared by the following method: S51, adding functional monomers and polyols to an organic solvent, adding alkaline materials, stirring at room temperature for 15-30 hours, cooling to 0°C, slowly dripping saturated salt solution into the reaction solution for extraction, concentrating the extract by evaporation, and separating by chromatography to obtain a reaction product A, wherein the mass ratio of functional monomers, polyols, organic solvents, and alkaline compounds is (80-120): (100-150): (9000-10000): (0.5-2.5); S52, mixing the reaction product A, deionized water, and the alkaline compound at 60-150° C. for reaction, slowly adding the epoxy compound, and controlling the pressure in the reactor to be 0.2-0.8 MPa for hydrothermal reaction, cooling to room temperature after the reaction, and centrifugation drying to obtain a reaction product B, wherein the mass ratio of the reaction product A, deionized water, the alkaline compound, and the epoxy compound is: (100-120): (50-200): (0.3-0.8): (80-150); S53, adding a functional modifier into deionized water, adding 0.05-0.2 mol / L of a buffer reagent to adjust the pH of the solution to 7-10, adjusting the reaction temperature of the solution to 40-60°C, adding the reaction product B into the mixed solution for reaction for 0.5-1.5h, then heating to 90-120°C for reaction for 2-8h, cooling to room temperature after the reaction is completed, adding ethanol for precipitation and centrifuging to obtain a sulfonic acid group-modified functional monomer, wherein the mass ratio of the functional modifier, deionized water, and the reaction product B is: (10-30): (20-80): (5-40); S54, after mixing the sulfonic acid group modified functional monomer, polymer polysaccharide, unsaturated acid anhydride / ester and cross-linking agent, cross-linking reaction is carried out at 20-60°C for 10-16 hours to obtain an enhancer, wherein the mass ratio of the sulfonic acid group modified functional monomer, polymer polysaccharide, unsaturated acid anhydride / ester and cross-linking agent is: (5-30): (5-10): (15-60): (0.05-1).

3. The method for preparing a functional fiber modifier according to claim 2, characterized in that: In step S51, the functional monomer is one or more of 4-hydroxybutyl vinyl ether, ethylene glycol monovinyl ether, 2-chloroethyl vinyl ether, and isopentyl glycol ether; The polyol is one or more of propylene glycol, ethylene glycol, propylene glycol, glycerol, mannitol, xylitol, sorbitol, polyether diol, 1,2,4-butanetriol, and trihydroxymethylpropane; the organic solvent is any one of dimethyl sulfoxide, N-methylpyrrolidone, butanone, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, ethyl acetate, N,N-dimethylformamide, and acetone; The alkaline material is one or more of lithium diisopropylamide, sodium hydride, sodium methoxide, potassium methoxide, sodium ethoxide, lithium diisopropylamide, butyl lithium, potassium ethoxide, sodium tert-butoxide, and sodium cyanide; The saturated salt solution is any one of saturated solutions of sodium chloride, potassium bromide, ammonium sulfate, strontium nitrate, lithium chloride, magnesium chloride, barium chloride, magnesium nitrate and potassium chloride.

4. The method for preparing a functional fiber modifier according to claim 2, characterized in that: In step S52, the alkaline compound is one or more of N-methyldiethanolamine, diglycolamine, dimethylethanolamine, and triethanolamine; The epoxy compound is one or more of propylene oxide, butylene oxide, ethylene oxide, epichlorohydrin, propyl ethylene oxide, and methyl propylene oxide.

5. The method for preparing a functional fiber modifier according to claim 2, characterized in that: In step S53, the functional modifier is one or more of methanedisulfonic acid disodium salt, sodium styrene sulfonate, sodium alkyl sulfonate, sodium alkylbenzene sulfonate, sodium vinyl sulfonate, sodium propylene sulfonate, sodium methyl propylene sulfonate, sodium styrene sulfonate, 2-acrylamide-2-methylpropane sulfonic acid, sodium alkyl sulfate, sodium alkyl naphthalene sulfonate, sodium alkyl succinate sulfonate, and sodium aminosulfonate; The buffer reagent is at least one of hydroxymethylaminomethane-hydrochloric acid buffer, potassium dihydrogen phosphate-disodium hydrogen phosphate, boric acid-borax, N-2-hydroxyethylpiperazineethanesulfonic acid buffer, glycine-sodium hydroxide, trishydroxymethylaminomethane hydrochloride, acetic acid-sodium acetate, 2-(N-morpholino)ethanesulfonic acid, disodium hydrogen phosphate-citric acid, and phosphate buffer solution.

6. The method for preparing a functional fiber modifier according to claim 2, characterized in that: In step S54, the polymer polysaccharide is one or more of sodium alginate, dextran sulfate, sodium carboxymethyl cellulose, sodium cellulose sulfate, sodium cellulose carboxylate, carboxycellulose, carboxymethyl chitosan, potassium carboxymethyl cellulose, guar gum, xanthan gum, carrageenan, carboxymethyl cellulose, and methyl cellulose, wherein the carboxymethyl chitosan is O-carboxymethyl chitosan or N,O-carboxymethyl chitosan; The unsaturated acid anhydride / ester is one or more of acrylic anhydride, 1,3-butanediol dimethacrylate, 1,3-butanediol diacrylate, methacrylic anhydride, ethylene glycol dimethacrylate, methyl methacrylate, ethyl methacrylate, 1,4-butanediol dimethacrylate, 1,4-butanediol diacrylate, ethylene glycol diacrylate, 1,3-propylene glycol dimethacrylate, and 1,3-propylene glycol diacrylate; The cross-linking agent is one of persulfate, water-soluble azo compound and peroxide, wherein the persulfate is one or more of sodium peroxydisulfate, benzoyl peroxide, potassium peroxydisulfate, ammonium persulfate, sodium persulfate, sodium permonosulfate and potassium permonosulfate; the water-soluble azo compound is one or more of azobisisobutylamidine hydrochloride or 2,2'-azo[2-(2-imidazoline-2-yl)propane] dihydrochloride, azobisisobutyric acid and azobisisobutylamidine; the peroxide is one or more of hydrogen peroxide, peroxycarboxylic acid and perborate.

7. The method for preparing a functional fiber modifier according to any one of claims 1 to 6, characterized in that: The calcium raw material is one or more of quicklime, calcium carbonate, calcium nitrate, calcium formate, calcium acetate, calcium chloride, calcium gluconate, calcium hydrogen phosphate, calcium lactate, and calcium chloride; The siliceous raw material is one or more of silica gel, silicon oxide, powdered quartz, silica fume, tetraethoxysilane (TEOS), silicon micropowder, analytically pure SiO2, sodium silicate, sodium metasilicate pentahydrate, potassium silicate, sodium metasilicate nonahydrate, and lithium silicate.

8. A functional fiber modifier, characterized in that: The functional fiber modifier is obtained by the preparation method of the functional fiber modifier according to any one of claims 1 to 7.

9. An application of the functional fiber modifier according to claim 8 in autoclave-free precast concrete, characterized in that: The following steps are involved: Weigh component materials according to the raw material formula and set aside, wherein the raw material formula includes the following component materials in parts by weight: 220-350 parts of cementitious material, 700-1050 parts of coarse aggregate, 500-850 parts of fine aggregate, 40-100 parts of admixture, 40-70 parts of functional fiber modifier and 50-70 parts of water, wherein the cementitious material includes organic cementitious material and inorganic cementitious material, wherein the mass ratio of inorganic cementitious material to organic cementitious material is 3:1; Firstly, coarse aggregate, fine aggregate and admixture are added into a forced mixer, and then inorganic gelling material is added and stirred to obtain a mixture; The functional fiber modifier is added into the mixture, and the mixture is stirred while being injected. Then, water and organic cementitious materials are added and the mixture is stirred continuously to obtain the steam-free precast concrete.

10. The use of the functional fiber modifier according to claim 9 in autoclave-free precast concrete, characterized in that: The inorganic cementitious material is one or more of silicate cement, aluminate cement, sulphoaluminate cement, lime or gypsum; The organic gelling material is one or more of polyacrylate emulsion, water-based acrylic resin, polyvinyl alcohol, water-based polyurethane resin, styrene-butadiene emulsion, vinyl laurate copolymer redispersible latex powder, water-based epoxy resin, guar gum, acrylic acid or acrylate homopolymer or copolymer redispersible latex powder, water-based alkyd resin, silicone-acrylic redispersible latex powder, ethylene-vinyl acetate copolymer emulsion, water-based fluorocarbon resin, and EVA dispersible rubber powder, wherein the EVA dispersible rubber powder is ethylene-vinyl acetate copolymer or homopolymer, and the ethylene content is higher than the vinyl acetate content; the polyvinyl alcohol is PVA1788, and its particle size is greater than 100 mesh; The admixture is one or more of fly ash, mineral powder, volcanic ash, silica powder or limestone powder.

Citation Information

Cited By

  • Conductive cement material and preparation method thereof

    CN121470854A